NCL-7, a novel all silica analog of polymorph B rich member of BEA family: synthesis and characterization - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
{Polymorph B-rich BEA type structure, NCL-7, was synthesized using hydrothermal method in fluoride medium using perchloric acid as promoter. The samples were characterized using XRD, low temperature N-2-adsorption and Si-29 MASNMR. As the structure of beta is highly disordered Rietveld refinement of powder XRD patterns is precluded. Phase composition is derived using the simulated patterns for the random intergrowths of polymorph A and B by DIFFaX. The stacking direction c' is perpendicular to the a'b' plane of the layer. The composition of polymorph B is found to be ca. 60-65%. Two other structures namely NCL-5 and NCL-6 with varying degree of polymorph B enrichment were also synthesized. Synthesis parameters such as effect of H2O/SiO2, TEAOH/SiO2, HClO4/SiO2 and crystallization temperature were studied thoroughly. The present article explains for the first time the synthesis and characterization of NCL-7, an analog of BEA type family with enrichment of polymorph B and its comparison with normal beta (*
Keywords: B-polymorph; DIFFaX; Promoter; Reitveld refinement; synthesis; zeolite beta

Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites

Tin-silicalite-1: synthesis by dry gel conversion, characterization and catalytic performance in phenol hydroxylation reaction - Niphadkar, Prashant S.; Kotwal, Mehejabeen S.; Deshpande, Shilpa S.; Bokade, Vijay V.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2009)
Tin-silicalite-1 (Sn-MFI) has been successfully synthesized by dry gel conversion (DGC) method. The influence of various synthesis parameters such as crystallization time, temperature, water content at the bottom of autoclave, molar ratios of (TPA)(2)O/SiO(2) and SiO(2)/SnO(2) in dry gel on the crystallization kinetics and physico-chemical properties of Sn-MFI materials has been investigated. Powder-X-ray diffraction (XRD),XPS,AAS, DRUV-vis and SEM techniques were employed as characterization tools. Time-dependent studies revealed that, the progressive crystallization of Sn-MFI depend not only on the synthesis time but also on the other various synthesis parameters. Increase in the crystallization temperature, water content at bottom of autoclave (TPA)(2)O/SiO(2) and SiO(2)/SnO(2) molar ratios in dry gel resulted in the lowering of overall crystallization period. A good correspondence between the chemical composition of the surface and the bulk indicated the uniform distribution of Sn(4+) ions. The presence of these ions in tetrahedral coordination has been indicated by DRUV-vis spectral studies. Although, not better but comparable activity has been shown by Sn-MFI prepared by dry gel conversion method with Sn-MFI prepared by conventional hydrothermal crystallization method in the hydroxylation of phenol reaction. Increase in concentration of isolated Sn(4+) ions led to increase in phenol conversion and H(2)O(2) efficiency. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: crystallisation; Dry gel conversion; microporous materials; Sn-MFI

Hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-methylphenol) using Sn/Si-MCM-41 catalysts - Garade, Ajit C.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (Chemistry Letters, 2010)
Sn/Si-MCM-41 has exhibited an excellent catalytic activity [70% product yield with 88% selectivity to 2,2'-methylenebis(4-methylphenol)] for the selective hydroxyalkylation of p-cresol. At equal level of Sn loading, Sn/Si-MCM-41 prepared by direct hydrothermal synthesis showed higher activity than Sn-impregnated Si-MCM-41 catalyst.

Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

Catalytic upgrading of renewable levulinic acid to ethyl levulinate biodiesel using dodecatungstophosphoric acid supported on desilicated H-ZSM-5 as catalyst - Nandiwale, Kakasaheb Y.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Patil, Vilas S.; Bokade, Vijay V. (Applied Catalysis A-General, 2013)
Levulinic acid (LA) is considered as a renewable platform chemical and can be used for the synthesis of variety of important fuels and chemicals. In particular, its esterification with ethanol produces ethyl levulinate (EL) would be green process, as it can be used as diesel miscible biofuel (DMB), preventing global warming by decreasing atmospheric CO2. This study explores the use of modified H-ZSM-5 by desilication viz.; DH-ZSM-5 and dodecatungstophosphoric acid (DTPA) loaded on DH-ZSM-5 for esterification of LA with ethanol aiming to EL. Different degree of desilication of H-ZSM-5 was performed by using aq. NaOH (0.2-1.5 M) at 338 K for 30 min and then DTPA was loaded on these desilicated H-ZSM-5 (DH-ZSM-5) support. H-ZSM-5, DH-ZSM-5 and DTPA on these DH-ZSM-5 samples were characterized by powder x-ray diffraction (XRD), N-2 adsorption-desorption, pyridine chemisorbed IR spectroscopy, Temperature Programmed Ammonia Desorption (TPAD). The increase in conversion of levulinic acid was observed from 28% to 94% with increase of DTPA loading from 0% to 15%. The increased LA conversion may be due to increase in total acidity from 43.14% to 84.31%. The use of DH-ZSM-5 as support for deposition of DTPA may be reported for the first time. The present work also extended to optimize process parameters such as DTPA loading on DH-ZSM-5, catalyst to LA ratio, LA to ethanol molar ratio, speed of agitation, particle size reaction temperature and catalyst reusability. Kinetic study based on pseudo-homogeneous (P-H) model is also presented. The experimental results follow second order kinetics. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: desilicated H-ZSM-5; DTPA on desilicated H-ZSM-5; Esterification; ethyl levulinate; levulinic acid

Dehydrogenation of cyclohexanol over Cu/Al2O3 catalysts prepared with different precipitating agents - Tangale, Nilesh P.; Niphadkar, Prashant S.; Deshpande, Shilpa S.; Joshi, Praphulla N. (Applied Catalysis A-General, 2013)
Dehydrogenation of cyclohexanol over Cu/Al2O3 catalysts (molar Cu:Al = 1:1) prepared by reduction of mixed oxide precursors synthesized using different precipitating agents viz, potassium carbonate, tetraalkyl ammonium hydroxides (TAAOHs) and urea was investigated. In order to assess the efficacy of TAAOH further, the chain length of tetraalkyl ammonium cations was also varied and the resulted catalysts were evaluated for their catalytic performance. The catalysts were characterized by powder X-ray diffraction, low temperature nitrogen adsorption, temperature programmed desorption of ammonia and UV-visible diffuse reflectance spectroscopy. The dependence of the catalyst performance on the precipitating agent employed during its synthesis has been clearly demonstrated. The use of TAAOH as precipitating agent led to the formation of a catalyst with better catalytic activity than those prepared using potassium carbonate and urea. Further improvement in the catalytic performance was observed when TAAOH with longer alkyl chain ammonium cation was used. The optimum catalyst prepared by reduction of mixed oxide precursor synthesized using tetrapropyl ammonium hydroxide as precipitating agent, showed highest cyclohexanol conversion (81.5%) and cyclohexanone selectivity (79.6%) at 250 degrees C on account of higher Cu+/Cu-0 ratio, well dispersed copper, higher surface area and lower total acidity with higher contribution of sites with moderate strength. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Characterization; Cu/Al2O3; Cyclohexanol dehydrogenation; Precipitating agent; Tetraalkyl ammonium hydroxide

Enhanced dual-effect of adsorption and photodegradation of SiO2 embedded TiO2 hybrid catalyst for improved decolourization of methylene blue - Sonar, Shilpa K.; Wagh, Reshma V.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Deshpande, Shilpa S.; Awate, Shobhana V. (Water Air and Soil Pollution, 2013)
Dual-effects of adsorption and photodegradation over titania, silica embedded titania, silica and commercial Degussa P-25 samples were studied for the decolourization of methylene blue in aqueous medium. Silica embedded titania and silica were prepared using inexpensive polymeric version of ethyl silicate as a source of silica. Catalysts were characterized by X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy and low temperature (77 K) nitrogen adsorption measurements. Among all the catalysts, silica embedded titania has exhibited faster decolourization of methylene blue solution on account of the enhancement of adsorption followed by degradation. An amount of the catalyst and the initial dye concentration of MB solution were found to influence the decolourization activity. Compared to titania catalyst, silica embedded titania and Degussa P-25 have shown the red shift in their UV-Vis spectrum. The experimental data of the reaction fitted well to the pseudo first order kinetic model. In present studies, the adsorption mechanism for the decolourization of MB solution was found to be applicable for an intra particle diffusion model.
Keywords: Adsorption; kinetic model; Methylene blue; Photodegradation; Silica embedded titania

Preparation and characterization of porous fly ash/NiFe2O4 composite: promising adsorbent for the removal of congo red dye from aqueous solution - Sonar, Shilpa K.; Niphadkar, Prashant S.; Mayadevi, S.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2014)
A series of fly ash/NiFe2O4 composites were prepared using fly ash and aqueous solutions of Ni, Fe nitrate salts and NaOH by co-precipitation followed by calcination method. The % mass ratio of fly ash: NiFe2O4 was varied in the range of 0:100 to 100:0. Samples were characterized by powder XRD, SEM, FTIR and N-2 adsorption-desorption measurements. These samples were further evaluated for their adsorptive performance in removal of Congo red (CR) dye from an aqueous solution. In all the composites, spinel nickel ferrite phase was found to be capable to get anchored with the fly ash surface and exhibited more crystalline nature as compared to pure NiFe2O4 phase. The BET surface area and porous character of the composite were found to increase with the decrease in the contribution of the fly ash, reach to maximum and then decreases on further decrease in fly ash. The composite having % mass ratio of fly ash: NiFe2O4 = 50:50 exhibited maximum CR adsorption from the aqueous solution on account of the higher BET surface area, more porous character, favorable condition for diffusion of dye molecules and combined effect of chemisorption and physisorption. Under optimum conditions, it has shown the recyclability with adsorption capacity of the magnitude 23.33 mg g(-1), which is much higher than individual fly ash, NiFe2O4 and other composites. The sorption data provided good fit with pseudo-second order kinetic model. The analyses of the adsorption data indicated that, the Langmuir model provides better correlation with the experimental data. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Composite material; Electron microscopy (SEM); Inorganic compounds; powder diffraction; Precipitation

Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Hierarchical K/LTL zeolites: synthesis by alkali treatment, characterization and catalytic performance in knoevenagel condensation reaction - Tangale, Nilesh P.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N. (Journal of Industrial and Engineering Chemistry, 2016)
The hierarchical K/LTL zeolites prepared by post-synthesis modification with aqueous 1.5 M KOH solution by varying alkali volume to K/LTL zeolite (10-70 ml/g) ratios, were examined in Knoevenagel condensation. The physico-chemical properties of the catalysts were thoroughly evaluated by PXRD, ICP, CO2-TPD, XPS, N-2 adsorption/desorption and Si-29 and Al-22 MAS-NMR. Among all the samples, hierarchical K/LTL prepared by treating K/LTL with 50 ml aqueous 1.5 M KOH solution per gram of K/LTL displayed about 1.5 fold higher catalytic activity as compared to parent K/LTL, presumably because of combined effect of enhanced basicity and molecular diffusion through pore channels. (C)2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Basicity; Hierarchical zeolite; K/LTL; Knoevenagel condensation; Micro-mesoporous composite

KLTL-MCM-41 micro-mesoporous composite as a solid base for the hydrogenation of sugars - Tangale, Nilesh P.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Dhepe, Paresh L. (Catalysis Science & Technology, 2018)
An approach to the synthesis of KLTL-MCM-41 micro-mesoporous composites of varying SiO2/Al2O3 molar ratio (20-8) was designed by following green technology. The synthesis was based on the recycling of waste mother liquor containing preformed KLTL zeolite crystals and unutilized reagents. The micro-mesoporous composites consist of KLTL zeolite crystals preformed through hydrothermal treatment in the first step. In the second step, the siliceous mother liquor was transformed into mesoporous MCM-41. The physico-chemical properties of the KLTL-MCM-41 micro-mesoporous composites were determined by PXRD, ICP-OES, FTIR, CO2-TPD, Al-27 MAS-NMR, TEM-EDX, HRTEM, and N-2 adsorption-desorption measurements. The mesopores properties of the KLTL-MCM-41 composites depended on the SiO2/Al2O3 molar ratio. The characterization results led to the following conclusions with decreasing SiO2/Al2O3 molar ratio: 1) decreasing order of the mesophase, 2) decreasing wall thickness of the mesopores, and 3) decreasing BET surface area and pore volume. Al-27 MAS-NMR spectra showed that only tetrahedrally coordinated aluminium was contained in zeolite KLTL. Moreover, the total amount and the strength of the basic sites of the KLTL-MCM-41 micro-mesoporous composites owing to the exchangeable potassium content (Al/K ratio approximate to 1) decreased in the order: 8 MMC > 10 MMC > 15 MMC > 20 MMC. The catalytic activity of the synthesized micro-mesoporous samples as a solid base was tested for the hydrogenation of xylose to sugar alcohols